Electrodeposition and characterization of conducting polymer films - Ng, Han Wah. (2008)
Several different methods and alternative polymers have been utilized for fabricating polymer LEDs. Electrochemically deposition of polyvinylcarbazole in LED applications is a new approach. Copolymers of bithiophene and vinylcarbazole were deposited and characterized in this research work.